A decade since the International Year of Planet Earth - Earth Sciences for Society - BERBERT, Carlos Oití (2020)
Developed between 2007 and 2008, the International Year of Planet Earth (IYPE) was proclaimed by United Nations Organization with the objective to divulge the importance of the Earth Sciences for society and to alert for the main problems mankind will face in this Century related to ten big themes: Groundwater, Megacities, Climate, Earth crust and core, Natural disasters, Oceans, Natural resources (minerals) and Energy, Soils, Earth and health (or medical geology) and Earth and life. After ten years of the suggestions and recommendations to be developed by geoscientists there were important advances in some of those themes such as Climate, Earth crust, and core and Natural resources and Energy. In the other seven years, there was relatively few scientific or technological advances in the word. This shows that one decade was not enough for mankind to get knowing and solving the big problems itself caused and continues to cause to the planet. In spite of this, the Brazilian geoscientific community was sensitive to most of the IYPE themes and promoted the divulging of Earth sciences through workshops, symposia, congresses, classes, becoming one of the most active groups in the world.